Data for: "Host dependent specialized metabolism of nitrogen export in actinorhizal nodules induced by Frankia cluster-2" - Berckx, Fede; Pawlowski, Katharina (Swedish University of Agricultural Sciences, 2024)
The datafiles contain protein model structures as .pdb file format (Protein Data Bank) for the enzyme "2-oxoglutarate dehydrogenase/decarboxylase" of different Frankia species, in relation to the publication. These protein models were generated in silico on SWISS-Model website, using the crystal structure of Mycobacterium smegmatis (reference A0R2B1) and Staphylococcus epidermis (reference Q5HPC6) are templates. The modeling was performed using standard parameters, as described by the website instructions. The input data, namely amino acid sequences, were pulled from The National Center for Biotechnology Information (NCBI, Genbank) using a pBLAST search to identify the amino acid sequence from different Frankia species. The corresponding references to find these sequences are available as documentation files and in the supplementary data of the associated manuscript on the journal website. Each of the .pdb files contains information of one Frankia species, and is named after the corresponding species. For example, the datafile Falni refers to the model built for the protein of Frankia alni. These .pdb files are made available for those wishing to verify our conclusions. We recommend using protein visuallisation software, such as ChimeraX to open and visualise the data. The visualisation of the models are given in the supplementary figures.

Datafilerna innehåller proteinmodellstrukturer som .pdb file format (Protein Data Bank) för enzymet "2-oxoglutarate dehydrogenase/decarboxylase" av olika Frankia-arter, i relation till publikationen. Dessa proteinmodeller genererades i silico på SWISS-Model-webbplatsen, med användning av kristallstrukturen för Mycobacterium smegmatis (referens A0R2B1) och Staphylococcus epidermis (referens Q5HPC6) är mallar. Modelleringen utfördes med hjälp av standardparametrar, som beskrivs av webbplatsens instruktioner. Indata, nämligen aminosyrasekvenser, hämtades från The National Center for Biotechnology Information (NCBI, Genbank) med användning av en pBLAST-sökning för att identifiera aminosyrasekvensen från olika Frankia-arter. Motsvarande referenser för att hitta dessa sekvenser finns tillgängliga som dokumentationfiler och i tilläggsdata för det associerade manuskriptet på tidskriftens webbplats. Var och en av .pdb-filerna innehåller information om en Frankia-art och är uppkallad efter motsvarande art. Till exempel hänvisar datafilen Falni till modellen byggd för proteinet från Frankia alni. Dessa pdb-filer görs tillgängliga för att de slutsatser som vi drar i artikeln ska kunna verifieras. Vi rekommenderar att du använder programvara för proteinvisualisering, såsom ChimeraX för att öppna och visualisera data. Visualiseringen av modellerna ges i tilläggsfigurerna.
Data for: "Host dependent specialized metabolism of nitrogen export in actinorhizal nodules induced by Frankia cluster-2"
Keywords: carbon; kol; bacteria; nitrogen; kväve; bioinformatics; bioinformatik; protein modeling; proteinmodellering; Frankia; Frankia; Frankia; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)